Hydrogeomorphic and Spatio-Temporal Analysis of Riverine Wetlands in the Interfluvial Zone of Ganga and Sai Rivers, Uttar Pradesh, India - Maddheshiya S.K.; Jha M.; Tignath S.; Singh N. (My University, 2025)
An extensive riverine wetlands system, which includes two Ramsar sites, occurs in the interfluvial zone between the Ganga and Sai Rivers in the Gangetic plains. Channel avulsion has formed a system of sinuous channel wetlands and floodplain wetlands, such as oxbow lakes, meanders, complex scrolls, and the remnant of fluvial features that grew through erosional and depositional processes, resulting in riverine wetlands. These riverine wetlands are significant but endangered and threatened biodiversity hotspots. The study of spatial distribution and temporal change analysis of these riverine wetlands are very much necessary for assessment and management. Extraction, delineation and mapping of these riverine wetlands in the GIS environment using remote sensing data reveal that these riverine wetlands belong to an unstable fluvial system with low energy and high sediment yield. The spatio-temporal changes in the areal extent of these riverine wetlands have been assessed by an image-to-image change detection method based on spectral indices (NDVI and MNDWI) derived from satellite imagery from 2000 to 2019. The analysis showed that the floodplain wetlands are shrinking continuously, whereas the channel wetlands shrank up to 2014 and afterwards increased gradually due to rejuvenation activities; however, the overall trend is still decreasing with respect to the year 2000. Drought conditions prevail frequently, and extreme stress due to land use and land cover changes, along with the groundwater exploitation, will likely lead to continued declines in these unstable, low-energy riverine wetlands in the near future, which will ecologically and environmentally affect the interfluvial zone of the Ganga and Sai Rivers. © 2023, The Author(s), under exclusive licence to Society of Wetland Scientists.